Nadofaragene firadenovec: a breakthrough in the field of bladder oncology - Nadeem, Abdullah; Qamar, Khulud; Bilal, Wajeeha; Vohra, Laiba Imran; Ahsan, Areeba; Tariq, Rabeea (Frontiers in Urology, 2023)
Muscle-invasive bladder tumors pose a grave mortality risk due to their propensity for distant metastases. The therapeutic spectrum for such tumors encompasses surgery, chemotherapy, and radiation, tailored to the cancer’s severity. In the context of high-risk Bacillus Calmette-Guérin (BCG)-unresponsive non-muscle invasive bladder cancer (NMIBC), a novel treatment has emerged as a beacon of hope. Nadofaragene firadenovec, a pioneering gene therapy, has gained worldwide approval for combating this condition, marking a watershed moment in bladder cancer therapy. Nadofaragene firadenovec is ingeniously designed to address high-risk BCG-unresponsive NMIBC, particularly carcinoma in situ (CIS) with or without papillary tumors, in adult patients. Rooted in a vector DNA, this therapy encodes interferon (IFN)-2b, which imparts urothelial cells with the ability to generate IFN-2b. The resulting cascade of events triggers a multifaceted assault on cancer, characterized by its immunostimulatory, antiangiogenic, and apoptotic effects. The therapeutic efficacy of nadofaragene firadenovec rests on its capacity to exploit the transformed urothelial cells to deliver these targeted anticancer activities. The evolutionary trajectory of nadofaragene firadenovec culminated in its monumental approval in December 2022 by the United States, signifying a pivotal juncture in the field. Notably, a segment of patients, approximately 30%, prove refractory to BCG treatment. For these individuals, alternative therapeutic avenues are imperative. Presently, the landscape for patients with non-muscle invasive bladder cancer lacks a definitive, enduring solution. Against this backdrop, the introduction of nadofaragene firadenovec heralds a momentous stride toward the global availability of an authorized therapeutic intervention.